2022
DOI: 10.3389/fimmu.2022.955095
|View full text |Cite
|
Sign up to set email alerts
|

Severe aplastic anemia patients with infection who received an allogeneic hematopoietic stem cell transplantation had a better chance: Long-term outcomes of a multicenter study

Abstract: Background and aimsHow to select the treatment is a challenge for the management of acquired patients with infections. This study aimed at comparing the outcomes of SAA with infections who had an allogeneic hematopoietic stem cell transplantation (allo-HSCT)with that of patients who had an infection and received non-HSCT therapy.MethodsWe retrospectively compared the outcomes of patients with acquired SAA and infections who had an allo-HSCT (n = 141) with that of patients who had an infection and received non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Another study by the European Society for Blood and Marrow Transplantation (EBMT) (11) found the 10-year OS in VSAA patients treated with IST to be 73%, which is similar to our results. A Chinese study (12) also found that SAA and VSAA patients who underwent HSCT versus those who did not have comparable 6-year OS rates at 75.5% and 76.3%, respectively. Hu et al (13) found that patients with AA undergoing first-line IST had an early-death rate of 7.6%, with 86% of the early death occurring in those with VSAA.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study by the European Society for Blood and Marrow Transplantation (EBMT) (11) found the 10-year OS in VSAA patients treated with IST to be 73%, which is similar to our results. A Chinese study (12) also found that SAA and VSAA patients who underwent HSCT versus those who did not have comparable 6-year OS rates at 75.5% and 76.3%, respectively. Hu et al (13) found that patients with AA undergoing first-line IST had an early-death rate of 7.6%, with 86% of the early death occurring in those with VSAA.…”
Section: Discussionmentioning
confidence: 91%
“…But hematopoietic recovery after IST treatment often took at least 3 months ( 20 ), during which the patients were at risk for early death and loss of the opportunity for salvage therapy. In contrast, HSCT can restore neutrophils earlier and provide patients with a better chance of survival ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, HSC transplantation is mainly used to compensate for the lack of HSCs in patients with AA. However, there are complications associated with transplantation, such as graft-versus-host disease and risk of infection; therefore, the prognosis for patients with AA remains unsatisfactory (Liu et al 2022 ). The identification of cells with strong differentiation abilities would be extremely beneficial in the development of novel therapeutic strategies in clinical practice.…”
Section: Cell Reprogramming Alleviates Aa Hematopoietic Failurementioning
confidence: 99%
“…Relapse and clonal evolution are also obstacles in IST [ 9 , 10 ]. Therefore, AA patients still have unfavorable prognoses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%